PENGARUH TATA RUANG KANTOR TERHADAP EFISIENSI KERJA PEGAWAI) (Studi Kasus Pada Badan Kepegawaian Dan Pengembangan Sumber Daya Manusia (BKPSDM) Kota Malang) - Iska Arina; Yaqub Cikusin; Hayat Hayat (Sekolah Tinggi Pariwisata Mataram, 2021)
Important good space conditions are for employees, this will give encouragement to each individual employee to be able to work optimally. On the other hand, if the condition of the office space is not supportive, this will affect the implementation of its main tasks. One of the efforts to make the work run smoothly is to carry out every organizational activity based on efficiency, namely the best comparison between the efforts made and the results achieved. The purpose of this study is to provide direction in accordance with the results of the study based on the above problems, the objectives of this study are: To determine the effect of office layout on employee ork efficiency Agency for Personnel and Human Resources Development (BKPSDM) Malang City. The samples of this study were all employees totaling 45 people. Sampling using saturated sampling that is using all members of the population as a sample. The data collection method in this study used a questionnaire and documentation. The data analysis method used in this research is descriptive analysis and simple linear regression.The results of this study indicate that the office layout variable has a positive and significant effect on the work efficiency of employees at the Agency for Personnel and Human Resources Development (BKPSDM) Malang City.